POR UM PROJETO SÓCIO ESPACIAL DE DESENVOLVIMENTO (Revista de História Regional, 2007)
This article analyses subjects related to the space revalorization in the reconstruction of a critical social theory which should be necessarily based on the search for an ontological space. We tended to remark the importance of this subject defining the human existence course in wide terms, and in a particular project of development. Our aim is to work in a development spatial project of development that allows the enrichment of alternative proposals to the neoliberal model. In order to do that we started from an analysis of the spatial dimension of the traditional capitalism, and of its current transformations to the defence of a certain social-spatial project of development, previously defined as a proposal in course of construction.